A policy response to a downside of the integration of economies: An impossibility theorem - Oded Stark (University of Tübingen, Faculty of Economics and Social Sciences, 2014)
Recent research shows that the merger of economies increases aggregate stress. This paper shows that there is no income distribution policy which will ensure that the wellbeing of the individuals belonging to merging economies does not fall below their pre-merger level.
urn:nbn:de:bsz:21-dspace-530451
Keywords: D04; D63; F55; H53; P51; 330; Merger of populations; Revision of social space; Aggregate relative deprivation; Societal stress; Policy response